Ambiguitas Pembangunan Industri Minyak Kelapa Sawit di Boven Digoel: Ancaman atau Peluang terhadap Keamanan Komunitas Masyarakat Adat? - Audrea Denneisha; Arfin Sudirman (ECOTAS, 2022)
Boven Digoel was one of the first areas in Papua to meet the palm oil industry in the late 20th century. The palm oil industry’a arrival has changed the living conditions of the indigenous people who have occupied the Boven Digoel area for hundreds of centuries. Using community security and political ecology as the main concepts, this research seeks to determine how the development of the palm oil industry in Boven Digoel has caused and impacted the community security of the indigenous people. This study uses qualitative methods with document-based research, internet-based research, and interviews. The result shows that there is ambiguity in the interpretation of whether the way of life transformation indigenous Papuan people have been going through is considered as a loss. The current younger generation are easier to adapt to today’s modern stance. Meanwhile, before they experienced growth, the older generation had to feel loss first due to lack of knowledge and the many promises given during the land acquisition process. As a result of the change in the way of life, the ‘closeness to nature trait that have always been the trademark of the indigenous Papuan people has been fading.